The effect of laughter therapy on nursing students? anxiety, satisfaction with life, and psychological well-being during the COVID-19 pandemic: Randomized controlled study - ALPAR, ŞULE (My University, 2022)
Background: Changes in routine due to the pandemic have increased nursing students\" anxiety about clinical learning. The inadequacy experienced before graduation caused them to experience high levels of anxiety characterized by feelings of insecurity and unhappiness and negatively affected their life satisfaction.Method-ological studies are needed to confirm the efficacy of laughter therapy, which is effective in reducing anxiety and stress, on the online platform. The current study protocol was designed to evaluate the effect of online laughter therapy on anxiety, life satisfaction, and psychological well-being. Methods: Forty students were selected for the intervention group and forty students for the control group by assigning 1:1 with a real random number selector among 140 senior nursing students who made up the universe. The intervention group received ten sessions of online laughter therapy two days a week for five weeks. Par-ticipants in the control group did not receive any intervention during the study. Data were obtained at the beginning of the study and after five weeks with the \"State-Trait Anxiety Inventory\", \"Satisfaction with Life Scale\" and \"Psychological Well-Being Scale\".Results: After laughter therapy, the intervention result showed a significant increase in life satisfaction and psychological well-being scores (p < 0.001) and a significant decrease in anxiety scores (p < 0.001) in the intervention group compared to the control group. Conclusion: The study reveals that online laughter therapy significantly positively affects nursing students\" anxiety, life satisfaction, and psychological well-being.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; ENTEGRE VE TAMAMLAYICI TIP; Klinik Tıp; Klinik Tıp (MED); INTEGRATIVE & COMPLEMENTARY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Tamamlayıcı ve Manuel Terapi; Tamamlayıcı ve Alternatif Tıp; Complementary and Manual Therapy; Complementary and Alternative Medicine; Complementary therapies; COVID-19; Laughter therapy; Nursing; QUALITY-OF-LIFE; SOCIAL SUPPORT; YOGA; PROGRAM; BURNOUT; ADULTS; DANCE; WOMEN